Application of material assessment methodology in latent heat thermal energy storage for waste heat recovery. (1st February 2017) - Xu, Haoxin; Romagnoli, Alessandro; Sze, Jia Yin; Py, Xavier
Highlights: A comprehensive assessment methodology of PCMs for TES systems is proposed. Multi-Criteria Decision Making employed to build the methodology. Validation of methodology with building simulation from literature. Applied methodology to assess PCMs for WHR in cogeneration plant. Effective performance assessment reduces simulation in design of LHTES. Abstract: This study proposes a comprehensive and systematic methodology of Phase Change Materials assessment for Latent Heat Thermal Energy Storage design, which comprises prescreening, ranking and performance objective examination based on Multi-Criteria Decision Making tools. Firstly, a large candidate pool is pre-screened with crucial boundary constraints. The materials are then ranked by employing the Analytical Hierarchy Process and Techniques for Order Preference by Similarity to Ideal Solutions. Three distinctive objective functions are suggested to explicitly evaluate the performance of Phase Change Materials. Pareto solutions and Utopia points are additional tools in the performance objective examination. A good agreement observed between assessment results and a building thermal comfort simulation results from literature validated the proposed methodology. For the first time, performance assessment of Phase Change Materials with the methodology is carried out in an initial design phase of a Latent Heat Thermal Energy Storage system for Waste Heat Recovery application in a cogeneration plant. The performance of prescreened PCMs is evaluated and the results provides a clear ranking list and quantitative performance indicators which will provide a high level of confidence in selecting the best performing materials during the design phase.